PERBANDINGAN HASIL BELAJAR ANTARA SISWA YANG DIBERI TUGAS KELOMPOK DENGAN SISWA YANG DIBERI TUGAS INDIVIDU PADA MATA PELAJARAN AQIDAH AKHLAK DI KELAS VIII MTS NEGERI 2 KUANTAN SINGINGI TAHUN PELAJARAN 2022/2023 - Siska Indriani, Dewi (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2024)
The objective of the research was to find out the comparison of students’ learning result given group task treatment and those given individual task by giving the task directly to 8th-grade students of State Islamic School 2 Kuantan Singingi. The type of research was classroom act research. The subject of this research was the students of 8th-grade students class VIII.B that was given individual task treatment and students of class VIII.E that were given group task treatment. The data collecting technique was done by doing observation, test, and documentation. Based on the processed data, it was concluded the comparison of students’ learning result that were given group task treatment and those given individual task treatment in Akidah Akhlak subject in 8th grade of State Islamic School 2 Kuantan Singingi as follows: it was found that the students that were given individual task in cycle I got the mean class 84,08 while in cycle II the mean score was 86,52, meanwhile the class that was given group task the mean score in cycle I was 81,98 and in cycle 2 the mean score was 84,10. The factors that affected the result of students’ learning result between those given group task with those given individual task were as follows: the students given individual task were more active to accomplish the task compared to those given group task, because the group there were only about one or two students who were active in the process, meanwhile in accomplishing individual task the students were more active and independent. Tujuan penelitian ini adalah untuk mengetahui perbandingan hasil belajar antara siswa yang diberi tugas kelompok dengan siswa yang diberi tugas Individu melalui pelaksanaan metode pemberian tugas secara tidak langsung siswa kelas VIII Madrasah Tsanawiyah Negeri 2 Kuantan Singingi. Jenis penelitian ini merupakan penelitian tindakan kelas. Sebagai subjek dalam penelitian ini adalah seluruh Siswa-siswi di kelas VIII.B yang diberikan tugas secara individu dan siswa kelas VIII.E yang diberikan tugas secara Kelompok. Pengumpulan data dengan cara observasi, Tes, dan dokumentasi. Dari hasil pengolahan data dapat disimpulkan bahwa Perbandingan hasil belajar antara siswa yang diberi tugas kelompok dengan siswa yang diberi tugas individu pada mata pelajaran aqidah akhlak di Kelas VIII MTs Negeri 2 Kuantan Singingi adalah pada siswa yang diberi tugas Individu saat siklus I adalah 84,08 dan pada saat siklus II adalah 86,52 dan pada kelas yang diberi tugas Kelompok saat siklus I adalah 81,98 dan pada saat siklus II adalah 84,10. Faktor-faktor yang mempengaruhi perbandingan hasil belajar antara siswa yang diberi tugas kelompok dengan siswa yang diberi tugas individu adalah siswa yang diberi tugas individu lebih aktif mengerjakan soal dari pada siswa yang diberi tugas kelompok, dikarenakan dalam kelompok hanya satu atau dua orang saja yang aktif, pada tugas individu siswa lebih aktif dan bekerja secara mandiri.